2018
DOI: 10.7150/thno.27706
|View full text |Cite|
|
Sign up to set email alerts
|

CDC20 regulates cardiac hypertrophy via targeting LC3-dependent autophagy

Abstract: Rationale: Sustained cardiac hypertrophy often leads to heart failure (HF). Understanding the regulation of cardiomyocyte growth is crucial for the treatment of adverse ventricular remodeling and HF. Cell division cycle 20 (CDC20) is an anaphase-promoting complex activator that is essential for cell division and tumorigenesis, but the role of CDC20 in cardiac hypertrophy is unknown. We aimed to test whether CDC20 participates in the regulation of pathological cardiac hypertrophy and investigate the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 29 publications
(33 reference statements)
2
34
0
Order By: Relevance
“…ardiac-specific deficiency of ATG5 results in left ventricular hypertrophy, dilatation, and contractile dysfunction and mitochondrial misalignment and aggregation at 1 week after pressure overload ( 18 ) However, the role of autophagy in cardiac hypertrophy requires further study. our data revealed that 2, 5 6 β5i KO but further enhanced by overexpression of β5i in primary cardiomyocytes and in the heart (Figs. 2, F and G, 5E, and 6E).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…ardiac-specific deficiency of ATG5 results in left ventricular hypertrophy, dilatation, and contractile dysfunction and mitochondrial misalignment and aggregation at 1 week after pressure overload ( 18 ) However, the role of autophagy in cardiac hypertrophy requires further study. our data revealed that 2, 5 6 β5i KO but further enhanced by overexpression of β5i in primary cardiomyocytes and in the heart (Figs. 2, F and G, 5E, and 6E).…”
Section: Discussionsupporting
confidence: 57%
“…Subjection to TAC for 2 to 4 weeks usually induces the expression of ATG5, ATG6/Beclin-1, ATG16L1, and LC3-II, leading to the induction of autophagy in the heart ( 21 , 22 ). asic autophagy is required for the physiological maintenance of cellular homeostasis, but excessive autophagy or insufficient autophagy may influence cell survival, cardiac hypertrophy, and HF ( 24 , 25 ). To date, the beneficial role of autophagy in hypertrophic remodeling remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptation of protein turnover is a key process of cardiac hypertrophy, which is the balance between protein synthesis and degradation (Ullrich et al, 2019). The main mechanism controlling protein degradation is the ubiquitin-proteasome system, which is important for many cellular processes, including apoptosis (Xie et al, 2018). We showed that siRNA-SLC26A4 treatment could promote apoptosis of cardiomyocytes induced by PE, indicating that inhibiting SLC26A4 could remodel cardiac structure after cardiac hypertrophy through the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 85%
“…It has been found that changes in autophagosome-lysosomal pathway activity have key pathogenic effects in cardiac hypertrophy (Ba et al, 2019). Autophagy at the normal levels protects cardiomyocytes from environmental stimuli, but autophagy imbalance can lead to cardiac hypertrophy (Xie et al, 2018). Therefore, cardiomyocyte autophagy plays an important role in maintaining myocardial function.…”
Section: Introductionmentioning
confidence: 99%